The future is now!: extrapolated riskscapes, anticipatory action and the management of potential emergencies - Neisser, Florian; Runkel, Simon (Geoforum, 2017)
Anticipating the future is a key practice for the management of potential emergencies. Anticipatory action needs the future to become ready-to-hand. Focusing on the logics and practices of anticipatory action the paper discusses the relations between time and space in the context of risk and uncertainty. Spatializations of simulation technologies, preemptive emergency management and anticipatory action aim to disclose and extrapolate the future. In general, infrastructures are technologies which aim to materialize expectations concerning the future. In the case of emergency management infrastructural measures enable and/or constrain practices by inheriting specific logics. The concept of riskscapes (Müller-Mahn and Everts, 2013) poses to be a promising framework to grasp these issues. In our perspective, extrapolated riskscapes treat the future as an already interpreted and symbolically structured world. This involves not only looking at the temporality of riskscapes, but also dealing with geographies of inscribed futurity. Two case studies focusing on emergency management practices of firefighters will be deployed for illustration: the first observes the logics of preemptive emergency management and anticipatory action inscribed into materialities of infrastructures in the context of rail-bound hazmat transports; the second shows how computer simulations for crowded geographies facilitate decision-making and action for policing and crowd management. Instead of treating future in riskscapes as neutral, we highlight the politically situated practices that co-evolve with these technologies and their spatializations. The article discusses the dimension of time within riskscapes to gain a better understanding of the temporalization of space as in simulations and the spatialization of time as in infrastructures of emergency management.